Specialised sweetpotato vine multiplication in Lake Zone, Tanzania: What “sticks” and what changes? - McEwan, M.; Lusheshanija, D.; Shikuku, Kelvin Mashisia; Sindi, K. (Walter de Gruyter GmbH, 2017)
In Lake Zone, Tanzania, farmers were trained to multiply and distribute quality sweetpotato planting material. The objectives of this study were to assess changes in skills and practices among the trained farmers as vine multiplication became a specialized task. Nine months after the project ended, all 88 decentralized vine multipliers (DVMs) operating as groups (72%) or individuals (28%) were visited and qualitative data on their current multiplication practices collected through a questionnaire, checklists and observations. Results showed that 69% of DVMs were still multiplying vines, but less than half were using the seed production technologies promoted by the project. 34% used rapid multiplication beds; 61% used conventional plant spacing on ridges for roots and vines and 5% used both. As the vine multiplication cycle became a specialised activity, the multiplication and root production cycles were separated. Vines were treated differently in terms of site selection, length of cutting and spacing, depending on whether the objective of their use was for high root or high vine production. Capacity building of specialised vine multipliers and scaling-up seed interventions should consider the implications of skilling and task segregation in a broader context based on society’s choice of technologies and agrarian change.